Debt financing and firm performance: empirical evidence from the Pakistan Stock Exchange. Issue 3 (8th March 2021) - Nazir, Aamir; Azam, Muhammad; Khalid, Muhammed Usman
Abstract : Purpose: The purpose of this study is to investigate the relationship between the listed firms' debt level and performance on the Pakistan Stock Exchange (PSX) during a five-year period. Design/methodology/approach: This study uses pooled ordinary least squares regression and fixed- and random-effects models to analyse a cross-sectional sample of 30 Pakistani companies operating in the automobile, cement and sugar sectors during 2013–2017 ( N = 150). Findings: The results indicate that both short- and long-term debt have negative and significant impacts on firm performance in profitability. This suggests that agency issues may lead to a high-debt policy, resulting in lower performance. However, both sales growth and firm size have positive effects on the profitability of non-financial sector companies. Research limitations/implications: This study suggests that when debt financing significantly and negatively influences firm profitability, company owners and managers should focus on finding a satisfactory debt level. However, this study is limited to the automobile, cement and sugar sectors of Pakistan. Future studies could address other sectors, such as textiles, fertilizers and pharmaceuticals. Originality/value: This study focusses on enhancing the existing empirical knowledge of debt financing's influence on the PSX's major sectors' profitability.